Management of primary mycotic aneurysms and prosthetic graft infections: an 8‐year experience with in‐situ cryopreserved allograft reconstruction. Issue 9 (12th August 2020) - Arasu, Rohan; Campbell, Ian; Cartmill, Andrew; Cohen, Toby; Hansen, Peter; Muller, Juanita; Dave, Richa; McGahan, Timothy
Abstract: Background: Primary mycotic aneurysms and prosthetic graft infections are traditionally managed by resection of infected vascular tissue and revascularisation with an extra‐anatomical bypass. Long‐term patency for this method has been reported to be poor with associated high reinfection and limb amputation rates. The aim of this study was to analyse the outcomes of those patients in our department between 2010 and 2018 whom had revascularisation with in‐situ arterial reconstruction using cryopreserved allograft as a conduit. Methods: The data were retrospectively reviewed and 13 patients were identified. There were five patients with primary mycotic aneurysms and eight patients with prosthetic graft infections, three of which were complicated by aortoenteric fistulae (AEF). Results: There were three peri‐operative mortalities (23%) with all three mortalities related to graft re‐infection and post‐implantation haemorrhage; two of these from uncontrolled bile leaks related to the original AEF with persistent graft contamination. The 10 surviving patients were followed up for a mean duration of 15.8 months with an overall primary graft patency of 89% and no incidence of graft re‐infection or aneurysmal degeneration. Conclusion: Patients that survived the peri‐operative period demonstrated acceptable medium‐term allograft durability, with the most favourable outcomes observed in those patients who had arterial infections uncomplicated by AEF. The main barrier to more wide‐spread use in our state remains inadequate supply of banked cryopreserved tissue. Abstract : This study is an original research paper analysing and discussing the outcomes of patients who had either prosthetic graft infections or primary mycotic aneurysms who then went on to have surgical management with in‐situ arterial reconstruction using a cryopreserved allograft.